An investigation into the mechanics of powered rotary tillage tools - Thakur, Tara Chandra. (Cranfield University, 1985)
A prediction model based upon Mohr-Coulomb soil mechanics theory has been developed to predict the itneraction between the soil and a rotary tiler blade with horizontal axis of rotation by neglecting the quasi-static reaction and the dynamic soil reactions due to acceleration of the deformed soil slice and sinkage of the chamfered back face of the blade as a special case. The quasi-static force prediction model is dependent upon the passive general shear failure of the soil slice towards the curved free surface of a previous cut and the lateral local shear failure towards the undeformed soil due to the effect of the tip. Cont/d.